Evaluation of the Valine requirement of small-framed first cycle laying hens. (16th October 2018) - Wen, J; Helmbrecht, A; Elliot, M A; Thomson, J; Persia, M E
ABSTRACT: An experiment was conducted to evaluate the total Valine (Val) requirement of first cycle laying hens from 41 to 60 wk of age. A total of 270 Hy-line W-36 laying hens were randomly assigned to 6 treatments with 15 replicate groups of 3 birds for each experimental unit. A Val deficient basal diet was formulated with corn and peanut meal with analyzed Val, Lys and crude protein concentrations of 0.515, 0.875, and 13.38%, respectively. Synthetic L-Val was supplemented to the basal diet in 0.070% increments to generate experimental diets containing 0.515, 0.585, 0.655, 0.725, 0.795, and 0.865% Val respectively. A controlled feeding program was applied during the experiment resulting in approximately 95 g feed intake per hen per day. Linear broken line, quadratic broken line, quadratic polynomial and exponential models were used to estimate the Val requirement of the hens based on hen-housed egg production (HHEP), egg mass (EM), and feed conversion ratio (FCR). Hen-housed egg production ranged from 48.3 to 81.4%, dependent upon dietary concentration of Val. Val requirements estimated by linear broken line, quadratic broken line, quadratic polynomial and exponential models were reported. Using the linear broken line model, the Val requirement was highest for egg mass, 597.3 mg/d, followed by egg production, 591.9 mg/d and lowest for FCR, 500.5 mg/d.